Morphology, structure, optical property and photoelectrochemical property of TiO2 nanoflower films synthesised via liquid phase deposition technique. (1st April 2014) - Rahman, M.Y.A.; Umar, A.A.; Roza, L.; Salleh, M.M.
Abstract : This reported study was concerned with the synthesis of TiO2 nanoflowers as a photovoltaic material of the photoelectrochemical cell (PEC) via the phase liquid deposition technique. It highlighted the effect of the growth time on the morphology of TiO2 samples. Three growth times were chosen, namely 2, 4 and 6 h. The morphology was examined by scanning electron microscopy (SEM). The nanoflowers' morphology of the TiO2 sample grown for 4 h was then chosen to be characterised by cross‐sectional SEM, X‐ray diffraction, ultraviolet–visible and photoelectrochemical measurement. The sample was crystalline with anatase phase. The sample showed the strongest absorption at 330 nm. The TiO2 nanoflowers PEC demonstrated the J sc and V oc of 0.046 mAcm −2 and 0.26 V, respectively.